The Effect of [2-(9-anthryl) -3- (1,3,4- Triazole -1- yl) -2,3- Dihydro -5,6- ene â€“ 1,3- Oxazepine- 4,7-Dione] on Serum AST and ALT Activities - Jasim, H. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study , the effect of an organic compound prepared as derivative of oxazepine tested on the activities of aspartate amino trasferase (AST) and alanin amino transferase (ALT). The kinetic study of such enzymes is in the presence of oxazepine derivative.  The results revealed that the organic compound is a non competitive inhibitor for both enzymes.  The Km value for AST is 1.3 Ã— 10-3 M and Vmax for the uninhibited is 200 U/mL and for the inhibited is 111.1 U/mL while Km value for ALT is 2.5 Ã— 10-3 M and Vmax are 89.66 U/mL and 56.77 U/mL for the uninhibited and inhibited enzyme respectively.